On Generation, Motions, and Collisions of Dowsons - Pieranski, Pawel; Godinho, Maria Helena (Frontiers in Physics, 2020)
Dowsons are ±2π point singularities of the unitary complex order parameter eiφ characterizing the so-called dowser texture in a thin nematic layer with homeotropic boundary conditions. Dowsons are therefore similar to disclinations in freely-standing smectic C films or to vortices in two-dimensional superfluids or superconductors. Using especially tailored setups called dowsons' colliders, pairs of dowsons of opposite signs are generated and set into motion on counter-rotating trajectories leading to collisions. In a first approximation, the velocity of dowsons is orthogonal and proportional to the local phase gradient ∇⃗φ. The outcome of collisions, i.e., either annihilation or bypass, depends on the distance of trajectories Δφ in terms of the phase: for Δφ < π a collision of a pair of dowsons leads to their annihilation, while for Δφ > π the dowsons are passing by. This rule is valid only for quasi-static stationary wound up textures and can be easily broken by application of a Poiseuille flow in an appropriate direction.